2020
DOI: 10.1007/s42979-020-00325-6
|View full text |Cite
|
Sign up to set email alerts
|

The FaceChannel: A Fast and Furious Deep Neural Network for Facial Expression Recognition

Abstract: Current state-of-the-art models for automatic facial expression recognition (FER) are based on very deep neural networks that are effective but rather expensive to train. Given the dynamic conditions of FER, this characteristic hinders such models of been used as a general affect recognition. In this paper, we address this problem by formalizing the FaceChannel, a light-weight neural network that has much fewer parameters than common deep neural networks. We introduce an inhibitory layer that helps to shape th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Analysing the different data sets in Figure 3, we believe that certain data enhancements will strengthen the image information and improve the recognition accuracy. Because the original pixels of the data are too low, we directly extract the feature map of its local binary mode, which will enhance the texture information while losing more information [12]. Therefore, the speed is the fastest when the accuracy is the lowest.…”
Section: Results Analysismentioning
confidence: 99%
“…Analysing the different data sets in Figure 3, we believe that certain data enhancements will strengthen the image information and improve the recognition accuracy. Because the original pixels of the data are too low, we directly extract the feature map of its local binary mode, which will enhance the texture information while losing more information [12]. Therefore, the speed is the fastest when the accuracy is the lowest.…”
Section: Results Analysismentioning
confidence: 99%
“…The FaceChannel was recently formalized as a lightweighted convolutional neural network that is able to adapt towards different interaction scenarios. It showed to have a good adaptation towards novel scenarios [3,5], including the challenging task of recognizing affect during a Human-Robot Interaction setting [7].…”
Section: The Masked Face Channelmentioning
confidence: 99%
“…Recently, we proposed the FaceChannel [3], as a small and easy to adapt neural network, and evaluated it on different scenarios, including different fine-tuning methods. Our experiments showed that the network could be easily adapted due to its small number of parameters while maintaining good performance on most of the facial expression datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Affective Data To analyze subjects' facial expressions we used the FaceChannel neural network [2]. The FaceChannel is a lightweight convolutional neural network that allows for fast training and fine-tuning of facial expressions.…”
Section: The Taskmentioning
confidence: 99%